TEACHING ENGLISH USING GAMES AND ACTIVITIES (Scientific Conference on Multidisciplinary Studies, 2025)
This article explores the dynamic practice of teaching English through games and activities. It delves into the theoretical foundations of game-based learning, examines the benefits and challenges of integrating both digital and traditional games into the curriculum, and offers practical strategies for designing engaging language lessons. The text also highlights how games can foster collaboration, boost motivation, and improve communicative competence while addressing common issues encountered by educators.